2002
DOI: 10.1038/nsb769
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of BLyS receptor recognition

Abstract: B lymphocyte stimulator (BLyS), a member of the tumor necrosis factor (TNF) superfamily, is a cytokine that induces B-cell proliferation and immunoglobulin secretion. We have determined the three-dimensional structure of BLyS to 2.0 A resolution and identified receptor recognition segments using limited proteolysis coupled with mass spectrometry. Similar to other structurally determined TNF-like ligands, the BLyS monomer is a beta-sandwich and oligomerizes to form a homotrimer. The receptor-binding region in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 40 publications
1
51
0
1
Order By: Relevance
“…However, calcium binding is an inherent property for C1q family proteins. TNF family proteins usually contain no metals, with few exceptions (25). According to our results, the conserved polar residue corresponding to Glu 1084 of hCap2_CRD is responsible, at least partially, for the intrinsic calcium binding nature of C1q family proteins.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, calcium binding is an inherent property for C1q family proteins. TNF family proteins usually contain no metals, with few exceptions (25). According to our results, the conserved polar residue corresponding to Glu 1084 of hCap2_CRD is responsible, at least partially, for the intrinsic calcium binding nature of C1q family proteins.…”
Section: Discussionmentioning
confidence: 85%
“…B-D, DAEA mutant, wild-type Cap2_CRD and the latter treated with EDTA were eluted from gel filtration column as trimer, a mixture of trimer and monomer, and monomer, respectively. However, their apparent molecular masses (25,14, and 9 kDa) calculated from gel filtration standard are obviously lower than expected for unknown reasons. E and F, dynamic light scattering analysis showed that wild-type hCap2_CRD and hCap2_DAEA both exhibit a single peak, and they have a similar average hydrodynamic radius with an estimated molecular mass (MW) of 60 kDa.…”
Section: Discussionmentioning
confidence: 99%
“…Like most members of the TNF family, the extracellular domain of TALL-1 can be cleaved to form a soluble cytokine (2). Crystal structure studies suggest that soluble TALL-1 (sTALL-1) 3 contains an unique "flap" region that is important for its virus-like assembly, receptor binding, and biological activities (7)(8)(9).…”
Section: Tnfr-associatedmentioning
confidence: 99%
“…The design of the fusion toxin was assisted by structural studies (39) suggesting that the trimeric nature and the COOH terminus of the natural BLyS molecule may be of critical importance to receptor recognition. We therefore designed this fusion toxin with the rGel component fused to the NH 2 terminus of the BLyS molecule.…”
Section: Construction Expression and Purification Of Rgel/ Blys Fusmentioning
confidence: 99%